Dealing with pollution from ships (HC, 2002)
This report focuses on the pollution contingency planning and response activities of the Maritime and Coastguard Agency. One of the Agency's responsibilities is to minimise the risk of pollution of the marine environment from ships and, where pollution occurs, minimise its impact on UK waters, coastlines and economic interests.